Managing energy-irrigation nexus in India: a typology of state interventions. - Mukherji, Aditi; Shah, Tushaar; Giordano, Mark (International Water Management Institute, 2012)
In this Highlight, historical antecedents of energy-irrigation nexus in India are examined and it has been found that its genesis lies in policy decision taken over two decades ago to supply unmetered electricity to farmers. This has led to a number of problems, most important of which is lack of appropriate incentive to all the players including farmers and utility officials to minimize perverse impacts and to ensure efficient use of power and groundwater. This in turn has led to a crisis in all three sectors - energy, groundwater and agriculture. In response, different state governments have tried different solutions to reduce negative impacts of this nexus. In this Highlight, a broad typology of these solutions is arrived at. It is concluded that solutions like universal metering and commercial power tariffs, though very effective and tried in a few states, are unlikely to be politically acceptable everywhere. In the meanwhile, second best solutions like feeder segregation and improving quality of power supply through technical interventions will have to suffice.